Retrospective analysis of stentgraft implantation in Department of Interventional Radiology and Neuroradiology of the 4th Independent Public Clinical Hospital in Lublin in 2016 - Izabela Dąbrowska; Andrzej Wolski (Kazimierz Wielki University, 2019)
Abdominal aortic aneurysm (AAA) is a localized enlargement of the abdominal aorta such that the diameter is greater than 3 cm or more than 50% larger than normal diameter. The abdominal aorta is the most common site of true arterial aneurysm affecting predominantly the segment of aorta below the renal arteries (intrarenal aorta). Well-defined risk factors are associated with the development of AAA and include older age, male gender, Caucasian race, a positive family history, smoking, the presence of other large vessel aneurysms and atherosclerosis. A retrospective analysis of clinical data of the patients admitted to Department of Interventional Radiology and Neuroradiology of the 4th Independent Public Clinical Hospital in Lublin was made. 33,3% of the implantations were performed as an emergency and life-saving procedures and according to our results higher risks of developing AAA are in male population and that risk is higher in older patients.